Capital Structure in Micro, Small and Medium Enterprises (MSMEs): Literature Approach - Martin Martin; Heri Pratikto (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research is a summary to highlight thoughts on capital structure in Micro, Small and Medium Enterprises (MSMEs). Deciding on the optimal capital structure is a very important managerial decision. Given the company's specificity in the MSME segment, achieving an optimal capital structure is a challenging task because there is no optimal capital structure model that can be universally applied in corporate practice. This study uses a literature review approach from journal publications that have been published for the last 5 years from 2016 to 2020. The results of the analysis obtained 86 journals and research on Capital Structure of Micro, Small and Medium Enterprises (MSMEs). From several journals collected, there are several similarities in terms of the grand theory used, namely the trade off theory, pecking order theory and agency theory.